Kronotop v groteskni strukturi romana Peterburg Andreja Belega - Skaza, Aleksander (Slavistična revija, 1997)
The paper discusses the "chronotopos" in the grotesque structure of Andrei Bely's novel Petersburg as a construction principle and as an axiological aspect in the formation of the literary characters' attitude towards the world. The turbulence of the grotesque "two-wordliness", i.e., changing the "normal world" to "topsy-turvy world", causes the literary characters to lose their temporal and spatial orientation or to even completely lose the temporaland spatial coordinates and gives rise to their ambivalent attitude towards the world.
Keywords: Belyj, Andrej; Belyj, Andrej: Peterburg; groteska; literarne študije; novel; roman; ruska književnost; Russian literature